2017
DOI: 10.1590/1980-5918.030.003.ar03
|View full text |Cite
|
Sign up to set email alerts
|

Assessment instruments of functioning in Brazilian elderly and the ICF: a systematic review

Abstract: Introduction: Under the new conceptual model described by the International Classification of Functioning Disability and Health (ICF) for a biopsychosocial health analysis, it is necessary to consider that it is not arising only from biological conditions, but also environmental, social, cultural and politics involved in this process. Objective: To review the publications that had the Brazilians elderly functioning as outcome by analyzing the instruments used and to verify its consistency with the ICF model. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
2
0
5
Order By: Relevance
“…Two reviews [17,18] identified a number of instruments which are more frequently used to assess functional capacity and/or mobility in older adults, including the Timed Up and Go test (TUG), the 6-Minute Walk Test (6MWT), Berg Balance Scale (BBS), Shuttle Test (ST), Ergometric Test (ET), and sit to stand chair test. Of note, some instruments assess physical performance by measuring lower limb function, such as the SPPB, which has been frequently used in Brazilian studies with older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Two reviews [17,18] identified a number of instruments which are more frequently used to assess functional capacity and/or mobility in older adults, including the Timed Up and Go test (TUG), the 6-Minute Walk Test (6MWT), Berg Balance Scale (BBS), Shuttle Test (ST), Ergometric Test (ET), and sit to stand chair test. Of note, some instruments assess physical performance by measuring lower limb function, such as the SPPB, which has been frequently used in Brazilian studies with older adults.…”
Section: Introductionmentioning
confidence: 99%
“…A quantidade de instrumentos ligados por cada um dos estudos diferiu, sendo que 37 (60,6%) estudos ligaram conteúdo de 2 a 6 instrumentos à CIF, 16 ( Quanto a metodologia de ligação, 1 estudo utilizou apenas o refinamento das regras de ligação 9 , 2 estudos utilizaram as regras propostas por Cieza et al 4 e Cieza et al 10 e seu refinamento 9 , 78,7% (n=48) dos estudos utilizaram as regras propostas por Cieza et al 4 Quanto à forma de expressar os resultados, houve estudos que demonstraram a ligação de cada item dos instrumentos à cada categoria CIF selecionada . Philbois et al 56 e Gomes et al 57 ligaram os itens dos instrumentos aos componentes da CIF. Campos et al 58 também demonstraram a ligação de cada item dos instrumentos às categorias CIF, porém, tais categorias advieram do core set para AVE e não da CIF completa.…”
Section: Resultsunclassified
“…O uso desse processo metodológico não é obrigatório, o que contribui para que estudos demonstrem outras metodologias de ligação, como o consenso e o nível de concordância entre avaliadores 61,62,78 . Porém, a não explicitação do método de ligação limita a reprodutibilidade do estudo, o que ocorreu nos estudos de Nickel et al 44 , Carvalho et al 34 , Josino et al 40 , Philbois et al 56 , Gomes et al 57 e Moura et al 54 . Dois estudos de revisão sobre a aplicação da CIF no Brasil identificaram Neurologia, Ortopedia e Reumatologia como os contextos mais frequentes 12,14 assim como os achados do presente estudo.…”
Section: Quadro 2 Continuaçãounclassified
“…Among the selected articles, there was no repetition of instruments for the analysis of functioning, nor a consensus on which tool to use to assess the given outcome. In contrast, Gomes, Buranello and Castro 22 found a physical test used in nine studies, by reviewing the instruments that assess functioning in the elderly. It was observed that the population affected with CHIK has pain and difficulties in moving one or some joints, mainly: ankles, wrists, hands, and knees 3,18,19 , compromising the functioning of individuals to perform their activities and interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%